DEEP VEIN THROMBOSIS IN PREGNANCY – RISK FACTORS, DIAGNOSIS, AND MANAGEMENT - Adorno, Ana Laura Vasconcelos de Pina; Silva, Luiza Aparecida Espindula da; Gomes, Isabella Pestana; Cardoso , Higor Chagas (CIPEEX, 2025)
INTRODUCTION: Pregnancy is a physiological state of hypercoagulability resulting from hormonal, hemodynamic, and hematological changes that increase the risk of venous thromboembolism (VTE), especially deep vein thrombosis (DVT). This condition represents one of the main causes of maternal morbidity and mortality, requiring early diagnosis and individualized management. OBJECTIVE: To analyze the primary risk factors, diagnosis, and treatment for this condition. METHODOLOGY: A literature review was conducted based on the analysis of five relevant articles published in the last five years and indexed in the PubMed database using the descriptors "Deep Vein Thrombosis", "Pregnancy", "Thrombophilia", and "Hypercoagulability”. RESULTS: The findings from these studies show that the incidence of DVT increases significantly during pregnancy, reaching its peak in the postpartum period. The literature highlights the main risk factors as hereditary thrombophilias, antiphospholipid syndrome, a previous history of VTE, advanced maternal age, obesity, immobilization, cesarean section, and assisted fertilization. Gestational DVT predominantly occurs in the left lower limb with greater iliofemoral involvement due to mechanical venous compression. The diagnosis combines clinical and imaging assessment, with Doppler ultrasound being the method of choice, and low molecular weight heparin (LMWH) is indicated as the safe and effective therapy for both treatment and prophylaxis. CONCLUSION: DVT in pregnancy is a high-risk condition that requires specialized attention. The early identification of risk factors, accurate diagnosis, and the timely introduction of anticoagulation are, therefore, fundamental measures to reduce maternal and fetal morbidity and mortality.